Pengaruh Penggunaan Tepung Ubi Jalar Ungu (Ipomea Batatas L) Terhadap Oksidasi Lemak, Kandungan Lemak, Antioksidan dan Derajat Keasaman (pH) Sosis Itik Manila: The Effect of The Use of Purple Sweet Flour on Fat Oxidation, Fat Content, Antioxidants and Acidity Degree (pH) of Manila Duck Sausage - Agatha Feriyanti Fore Kehik; Geertruida Margareth Sipahelut; Yakob Robert Noach (Universitas Nusa Cendana, 2023)
Research was conducted in order to find out the presentage of fat oxidation, fat content, antioidants, and acidity in manila duck sausage with the addition of purple sweet potato.. The design used was Completely Randomized Design (CRD) with five breatments and threereplications 5 treatments with 3 replications. Those treatments consisted of P0 = purple sweet potato flour 0% (20% tapioca)by using weight of meat, P1 = 5% purple sweet potato flour + tapioca 20%by using weight of meat, P2 = 10% purple sweet potato flour + 10% tapioca by using weight of meat, P3 = 15% purple sweet potato flour + 5% tapioca by using weight of meat, P4 = 20% purple sweet potato flour (0% tapioca). The variables studied were fat oxidation, fat content, antioxidants degres acidity pH. The results showed that the Ipomea batatas L had very significant effect (P<0.01) on antioxidants, fat oxidation as wel as significant effect (P<0.05) on increasing fat content and significantly affected on pH. the conclusion is that the use of Ipomea batatas L produces sausages with increased antioxidant activity and a decreased rate of fat oxidation, but the fat content does not change in manila duck sausage and can be used as a mixture in manila duck sausage. Penelitian dilakukan agar dapat mengetahui presentase oksidasi lemak, kandungan lemak, antioksidan, dan derajat keasaman pada sosis itik manila dengan penambahan tepung ubi jalar ungu. Racagan yang dipakai Rancangan Acak Lengkap (RAL) 5×3 yaitu 5 perlakuan ulangan 3 kali. Perlakuan ialah P0 = tepung ubi ungu 0% (tapioka 20%) sesuai berat daging, P1 = 5% tepung ubi ungu + tapioka 15% dari sesuai berat daging, P2 = 10% tepung ubi ungu + 10% tapioka sesuai berat daging, P3 = 15% tepung ubi ungu + 5% tapioka sesuai berat daging, P4 = 20% tepung ubi ungu (tapioka 0%). Parameter yang diuji ialah oksidasi lemak, kandungan lemak, antioksidan serta derajat keasaman (pH). Hasil penelitian menyatakan bahwa, perlakuan memiliki pengaruh sangat nyata (P<,0,01) pada antioksidan, oksidasi lemak serta berpengaruh tidak nyata (P<0,05) meningkatkan kandungan lemak lalu berpengaruh nyata terhadap pH. Kesimpulannya adalah penambahan Ipomea batatas L menghasilkan sosis dengan presentase antioksidan yang meningkat dan laju oksidasi lemak yang menurun namun kadar lemak tidak berubah pada sosis itik manila dan dapat di manfaatkan sebagai bahan campuran dalam sosis itik manila